Opportunity and incentive for becoming bilingual in Colombia: Implications for Programa Nacional de Bilingüismo - Herazo Rivera, José David; Jerez Rodríguez, Sonia; Lorduy Arellano, Danilza (Íkala, Revista de Lenguaje y Cultura, 2012)
The Programa Nacional de Bilingüismo (PNB) seeks to promote English proficiency in Colombian society in order to position Colombia within world communication processes, a global economy, and an increasingly multicultural world. Using documentary and statistical data within a case study approach, we characterize the PNB as a case of acquisition planning and argue that some of the social conditions that bolster bilingualism are not sufficiently developed in the Colombian context. Specifically, we maintain that the number of jobs requiring bilingual workers in Colombia’s labor market and the patterns of international mobility of Colombians provide little opportunity and incentive for developing bilingualism to the extent envisioned by the PNB. <!– [if gte mso 9]> <![endif][if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–>